Mycoremediation of high concentrations of polychlorinated biphenyls with Pleurotus sajor-caju LBM 105 as an effective and cheap treatment - Sadañoski, Marcela Alejandra (2019)
Polychlorinated biphenyls (PCBs) are exceptionally stable organic pollutants. An effective and economically feasible process is essential for their removal. Mycoremediation using white-rot fungal strains proved as a highly effective approach that has not been thoroughly investigated. The aim of this work was to evaluate PCBs remediation efficacy applying Pleurotus sajor-caju LBM 105. Axenic cultures of the fungus, either in complex or N-limited liquid media, were spiked with 217 mg L-1 of a technical mixture of Aroclor 1242, 1254 y 1260 in oil transformer. PCBs removal capacity, toxicity reduction, changes in fungal morphology and laccase expression caused by pollutant addition and the cost-effectiveness of the remediation treatment were assessed when growing the fungus under two different nutritional conditions. P. sajor-caju LBM 105 could remove 97.7% and 91.7% of the PCBs mixture and reduced the toxicity in complex and mineral media respectively after 35 days of incubation. The addition of PCBs to P. sajor-caju LBM 105 culture media resulted in an increase in hyphal diameter, changes in biomass, glucose consumption, proteins and laccase secretion. A 3-fold rise in laccase activity was detected in both media at 28 day. Laccase mRNA augmented 16% and 91% at 21 and 28 days respectively when PCBs were added to the N-limited liquid media. Mycoremediation of PCBs with P. sajor-caju LBM 105 cultivated in N-limited liquid medium is an effective low-cost (0.69 $ g-1d-1) alternative technique for PCBs treatment.